Renewal of challenging behavior in an intensive outpatient clinic: Replication and extension to task changes. - Aggarwal, Ishita; O'Brien, Matthew J.; Pauls, Alexander M.; Jeglum, Sara R.; Franck, Christopher T.; Martinez‐Perez, Carla N.; Podlesnik, Christopher A. (Journal of Applied Behavior Analysis (John Wiley & Sons, Inc.), 2026)
Retrospective analyses have shown that renewal of challenging behavior following person or setting changes is common. This study replicates and extends prior work by evaluating renewal after a third type of context change: task changes. Among 98 patients in an intensive outpatient clinic who experienced 749 context changes, overall renewal prevalence was 25.23% using a max‐of‐5 criterion (39.79% using a mean‐of‐2 criterion), consistent with prior reports across this large sample. Of the 63 patients who experienced at least one task change, 36 (57.14%) exhibited renewal. Task changes produced higher renewal rates than person or setting changes across criteria, but differences were not statistically significant. Renewal magnitude generally declined across sessions; however, challenging behavior rarely returned to prechange levels, even after five sessions. Findings highlight the broader range of contextual variables that may evoke renewal and the need for strategies to reduce its intensity and persistence during treatment.